2019
DOI: 10.1101/gad.328963.119
|View full text |Cite
|
Sign up to set email alerts
|

Cell-type-specific dysregulation of RNA alternative splicing in short tandem repeat mouse knockin models of myotonic dystrophy

Abstract: Short tandem repeats (STRs) are prone to expansion mutations that cause multiple hereditary neurological and neuromuscular diseases. To study pathomechanisms using mouse models that recapitulate the tissue specificity and developmental timing of an STR expansion gene, we used rolling circle amplification and CRISPR/Cas9-mediated genome editing to generate Dmpk CTG expansion (CTG exp ) knockin models of myotonic dystrophy type 1 (DM1). We demonstrate that skeletal muscle myoblasts and brain choroid plexus epith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…Several previous studies have examined DM1 mis-splicing events in various contexts (Jenquin et al, 2019;Nutter et al, 2019;Thomas et al, 2017;Wagner et al, 2016). Within our dataset, previously identified DM1-associated events were predominantly found at the myotube stage and examples include ARHGEF10L, BIN1, TNNT3, NCOR2, NUMA1, MBNL1, GOLGA4, and MEF2C (Fig.…”
Section: Dm1 Relevant Splicing Defects Appear In the Myotube Stagementioning
confidence: 84%
See 1 more Smart Citation
“…Several previous studies have examined DM1 mis-splicing events in various contexts (Jenquin et al, 2019;Nutter et al, 2019;Thomas et al, 2017;Wagner et al, 2016). Within our dataset, previously identified DM1-associated events were predominantly found at the myotube stage and examples include ARHGEF10L, BIN1, TNNT3, NCOR2, NUMA1, MBNL1, GOLGA4, and MEF2C (Fig.…”
Section: Dm1 Relevant Splicing Defects Appear In the Myotube Stagementioning
confidence: 84%
“…Alternative splicing is misregulated in DM1 and even more so in CDM1 patients leading to developmentally inappropriate RNA isoforms, eventually causing multisystemic DM1 symptoms (Nakamori et al, 2017;Thomas et al, 2017). In a DM1 mouse knock-in model, in which CTG expansions were inserted into the 3′ UTR of the mouse Dmpk gene, Nutter et al (2019) demonstrated that the expanded CTG repeat has more severe effects on muscle progenitor stages such as myoblasts and myotubes because of the higher expression of Dmpk at those stages and therefore higher capacity to sequester proteins leading to significant RNA mis-splicing (Nutter et al, 2019). Wagner et al (2016) proposed 46 aberrant splicing events related to DM1 that could serve as DM1 biomarkers (Wagner et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…As our statistical mechanics framework is agnostic to the identity of binding partners and considers only a distribution of binding energies, we anticipate that the same physical considerations by which DNA-binding proteins recognize STRs may also apply to RNA-binding proteins (RBPs). Evidence in the literature already points to a role for intronic STRs in regulating splicing (123)(124)(125)(126)(127)(128)(129)(130)(131)(132)(133) or promoting the formation of RNP compartments (134)(135)(136). These observations raise the intriguing possibility that STR-enriched enhancers could serve a dual function to bind TFs to regulate transcription and to subsequently recruit RBPs once transcribed into enhancer RNAs.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, dysregulation of cerebrospinal fluid (CSF) homeostasis was observed in early onset DM1. A study introducing DMPK CTG expansions into the mouse found that mis-splicing significantly affected brain choroid plexus epithelial cells ( Nutter et al, 2019 ). Besides, increased levels of total-Tau, IgG, γ-globulin, and myelin basic protein (MBP), as well as decreased levels of Aß1-42 and orexin-A were found in the CSF of DM1 patients ( Hirase and Araki, 1984 ; Martínez-Rodríguez et al, 2003 ; Winblad et al, 2008 ; Peric et al, 2014a ).…”
Section: Cellular Processes Alterationsmentioning
confidence: 99%